Odpowiedzi

2010-01-23T19:35:53+01:00
1.4x-2y=6 / * -3
3x+6y=12 / *4

-12x +6y = -18
12x + 24y = 48

30y=30
y=1

3x + (6*1) = 12
3x= 12-6
3x=6
x=2

x=2
y=1

2.2x-3y=-5
-x+5y=6 /*2

2x-3y=-5
-2x+10y=12
7y=7
y=1

-x + (5*1)=6
-x=6-5
x=1

x=1
y=1

3.3x-4y=14 /*2
-2x+7y=-18 /*3

6x-8y=28
-6x +21y = -54

13y=-26
y=-2

3x (-4*-2)=14
3x= 14 - 8
3x=6
x=2

x=2
y=-2



2010-01-23T19:37:56+01:00
1)
4x-2y=6 /*3
3x+6y=12

12x-6y=18
3x+6y=12
_________
15x=30 /:15
x=2

4*2-2y=6
8-2y=6
-2y=-2 /:-2
y=1

x=2
y=1

2)
2x-3y=-5
-x+5y=6 /*2

2x-3y=-5
-2x+10y=12
_________
7y=7 /:
y=1

-x+5*1=6
-x+5=6
-x=1
x=-1

x=-1
y=1

3)
3x-4y=14 /*2
-2x+7y=-18 /*3

6x-8y=28
-6x+21y=-54
___________
13y=-26 /:13
y=-2

3x-4*(-2)=14
3x+8=14
3x=6 /:3
x=2

x=2
y=-2
2010-01-23T23:34:10+01:00
1)
4x-2y=6|*3
3x+6y=12

12x-6y=18
3x+6y=12
15x=30
x=2

4*2-2y=6
-2y=-2
y=1

2)
2x-3y=-5|*5
-x+5y=6|*3

10x-15y=-25
-3x+15y=18
7x=-7
x=-1

2*(-1)-3y=-5
-3y=-3
y=1

3)
3x-4y=14|*7
-2x+7y=-18|*4

21x-28y=98
-8x+28y=-72
13x=26
x=2

3*2-4y=14
-4y=8
y=-2
1 3 1